Promoting change through the voices of Black graduate students: a qualitative exploration of the experiences of Black graduate students in MFT programs - Greene, Kamille Marie (Kansas State University, 2024)
This qualitative study explores the diverse experiences of Black students who are currently enrolled in, or recently graduated from, various marriage and family therapy (MFT) graduate school programs in the United States. This study uses minority stress theory and critical race theory to explore the lived experiences of Black graduate students at predominately White higher education institutions. The study sample includes 14 individuals (13 female, 1 male) that identify as Black graduate students in MFT programs across the United States. The study sample consists of seven students working towards a master’s degree and seven students pursuing a doctoral degree (PhD, D.A., etc.). Results were analyzed using the thematic analysis approach. The results indicate there are several barriers Black students in MFT graduate programs face including: financial concerns, racism, difficulty practicing self-care, lack of diversity within programs, and lack of support. The results also indicate support measures Black graduate students would have liked to see provided in their programs. These include mentorship, representation, and allyship. Implications based on the results are later discussed.
Keywords: Black graduate students; Minority Stress Theory; Critical Race Theory; Higher education; Marriage and family therapy